Peningkatan Kinerja Jaringan LAN Sekolah Menggunakan OSPF dan VLAN dalam Simulasi - Muhammad Rayhan Mumtaz; Zidane Tirta Nugraha; Deryl Timothy Hasiholan Pangaribuan; Johannes Siregar (Jurnal Riset Sistem dan Teknologi Informasi, 2026)
Reliable computer networks are crucial for digital transformation in schools but are often hampered by traffic bottlenecks and inefficient segmentation. This study aims to design and analyze an optimal school Local Area Network (LAN) using Cisco Packet Tracer simulation. The solution implemented is the multi-area OSPF dynamic routing protocol and VLAN segmentation to enhance efficiency and security. The simulation results demonstrate very high performance, achieving an average latency of only 3 ms and bandwidth utilization efficiency reaching 80%. This design proves an effective solution for providing a scalable and optimally performing network infrastructure for educational environments.